2019
DOI: 10.1515/multi-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

Being a journalist in a multilingual country: Representations of Dutch among Belgian French-speaking journalists

Abstract: In this paper, we examine how the francophone TV audience is introduced to the Flemish community and its language through daily news broadcasts. More specifically, our research looks at how the Dutch language is used when francophone journalists prepare and produce their reports – during all stages of the process –, up until the actual broadcast. We therefore conducted 15 qualitative interviews with TV news journalists employed by the Belgian French-speaking public broadcaster. The interviews were organized ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Our previous studies (Bouko et al, 2018;Standaert et al, 2020) revealed that Frenchspeaking reporters tend to admire bilingualism and frame it in an ideal way, in line with Bloomfield's idealized approach of 'the native-like control of two languages' (Bloomfield, 1933: 56). Although both French-and Dutch-speaking reporters admire bilingualism, claim that every Belgian should strive to be able to speak both most important official languages, and most feel embarrassed for their language levels, initiatives to make the newsroom more bilingual do not appear to be a reality.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our previous studies (Bouko et al, 2018;Standaert et al, 2020) revealed that Frenchspeaking reporters tend to admire bilingualism and frame it in an ideal way, in line with Bloomfield's idealized approach of 'the native-like control of two languages' (Bloomfield, 1933: 56). Although both French-and Dutch-speaking reporters admire bilingualism, claim that every Belgian should strive to be able to speak both most important official languages, and most feel embarrassed for their language levels, initiatives to make the newsroom more bilingual do not appear to be a reality.…”
Section: Discussionmentioning
confidence: 76%
“…In previous research on journalistic routines in the RTBF newsroom, the leading Belgian francophone TV broadcaster, we focused on French-speaking journalists’ representations and use of Dutch when covering a news story in Flanders, or when interviewing a (native) Dutch speaker (Bouko et al, 2018; Standaert et al, 2020) In this article, we compare these findings to those in the newsroom of the Flemish public broadcaster Vlaamse Radio- en Televisieomroep (VRT). An attempt is made at answering how Belgian TV reporters from either side of the language barrier regard the other linguistic community and its language through daily news broadcasts.…”
Section: Introductionmentioning
confidence: 99%